Multifocal HPV-Associated Anogenital Lesion: Histopathology in the Diagnosis of Penile Intraepithelial Neoplasia - Lita Setyowatie; Arika Latashia Adelia; Taufiq Nur Budaya; Diah Prabawati Retnani (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2026)
Introduction. Human papillomavirus (HPV) is a common sexually transmitted infection that can manifest as lesions ranging from benign conditions to premalignant disease. Case. We report the case of a 37-year-old widowed man who presented with multiple nodular lesions on the penis for one year and on the anus for seven months prior to seeking medical care. The patient had a history of Hodgkin lymphoma and had previously undergone chemotherapy. Physical examination of the penile shaft and pubic region revealed multiple erythematous papules with well-defined margins, irregular borders, and variable shapes and sizes. Examination of the anal and perianal regions revealed with similar characteristics. The diagnosis was established based on histopathological evaluation, which demonstrated distinct features at the two lesion sites. Biopsy of the genital lesions revealed findings consistent with Penile Intraepithelial Neoplasia (PeIN), supported by positive p16 immunohistochemical staining and HPV genotyping positive for HPV types 18 and 45, confirming HPV-associated Penile Intraepithelial Neoplasia. In contrast, biopsy of the anal lesions showed histopathological features consistent with condyloma acuminata. Conclusion. This report highlights the importance of clinical vigilance and the crucial role of histopathological examination in establishing an accurate diagnosis and guiding appropriate management, particularly in patients with risk factors for malignancy and a history of immunocompromised status.